Stained judgments, tarnished judges, tainted desire: The rhetoric of sexual orientation in South African judgments 1926-1999 - Montgomery, John Henry (My University, 2008)
Abstract This is a study of law and language; in particular an investigation into the language of judgments. The focus is on judgments as texts authored by judges. The main thinkers chosen as the theoretical basis are not experts in law – Michel Foucault, Mikhail Bakhtin, Norman Fairclough and Hayden White, for example. The reason for this choice is to consider the language of law from insights outside of law. Topics such as rhetoric, narrative, critical discourse analysis, intertextuality, interpretive communities, the monologic voice, oppositional reading, and power relations are seldom found in mainstream legal literature. The position taken is that judgments are texts which are no more privileged (simply because they are legal texts) than any others that a society creates. However, judgments are viewed by some as being special societal texts, coated with a patina of mystique because they are dealing with inviolate legal principles. The patina is removed enough to suggest that judges use various linguistic processes to shape their judgments in ways no different from other authors, notwithstanding that they are writing about ‘the law’. Judges are rhetoricians who use rhetoric to shape the facts, choose the most expedient legal principle, and incorporate views of society expedient to their opinion. The thrust of this study is to locate rhetoric at work within a specific sphere. The corpus consists of forty-four cases over a seventy-five year period dealing with sexual orientation. This area of law was chosen for a number of reasons. It is self-contained and lends itself to detailed examination. The topic is emotive which means more rhetorical techniques are at play than in a fairly technical area of law. There have been significant changes in the way sexual orientation has been treated in law over the years. It is interesting to trace how rhetoric facilitated that change. Lastly, we see how a judicial hegemony deals with an apolitical, splintered minority. Any categorical conclusions are impossible in an exploration of this kind. The findings, however, indicate that judges are not as restricted as is generally considered and that their judgments are shaped by employing linguistic techniques available to writers of both fact and fiction. The intention is to provide a fresh way of reading judgments, where observations gleaned in one area can be applied to other areas of law.
Keywords: Jurisprudence; rhetoric; discourse analysis; sexual orientation; homosexuality; sodomy; Foucault; historiography